Knowledge and management of mothers on diarrhea among children under five years old in Hospital Sultan Abdul Halim, Sungai Petani, Kedah - Alias, Nur Amalina (2016)
The objectives of the study were to find out the knowledge and to assess the management of mothers on diarrhea in children under five years old in Hospital Sultan Abdul Halim, Sungai Petani, Kedah.102 mothers with children of five years old and below at Hospital Sultan Abdul Halim, Sungai Petani, Kedah were surveyed. The data was collected from 29th April until 2nd May 2016. Most of the mothers were 25-30 years old (59.8 %). The highest percentage of family size was 3-5 people (78.4 %). There were no significant values among the mothers knowledge on diarrheal transmission when compared between ethnic, education and locality. However, there were a significant difference in the knowledge on mothers on prevention of diarrhea among ethnicity and locality. The management of mothers on diarrhea shows a significant difference among ethnics on homemade fluid and traditional healers while for giving ORS, there was a significant difference between education levels of the mothers. The knowledge and management of mothers about diarrhea in children under five years old in Hospital Sultan Abdul Halim, Sungai Petani, Kedah is high.